Comparison of Fetomaternal Outcome With/Without Use of Dates in Primigravidae at Term - Saima Iqbal, Sana Aftab, Saema Tehseen, Rozina Mustafa, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Effect of dates on pregnancy outcomes is in debate among researchers for optimum results. Aim: To compare the fetomaternal outcome with and without use of dates in primigravidae presenting at 37-38 weeks Main outcome: The outcome was measured as fetal (Apgar score at 5 min) and maternal (onset and induction of labor) parameters. Study design: Randomized controlled trial Setting: Department of Obstetrics and Gynaecology, District Headquarter Hospital, Gujranwala Duration of study: 6 months 1st January 2020 to 30th June 2020 Methods: A total of 110 patients reporting to OPD in their first pregnancy between 18 to 35 years of age at 37 to 38 weeks were included whereas multigravidae and those with previous miscarriage were excluded. Consecutive Non Purposive Sampling technique was used and patients were randomly divided in two groups of 55 each. Group A consumed dates in late pregnancy while Group B was asked not to. Duration of first and second stage of labour and Apgar score at 5 minutes were recorded. SPSS version 21 was used to enter and analyze the data. Quantitative variables Apgar score were presented in the form of mean ± SD. Qualitative variables like spontaneous labour, need for induction and good Apgar score were presented in the form of frequency and percentage. Chi-square test was applied to compare spontaneous labour, need for induction, and good Apgar score in both groups. P-value ≤0.05 was taken as significant. Results: The mean apgar score at five minutes was 8.76±1.157. The analysis of qualitative variables showed that spontaneous labor was started in 75(68.2%) of patients and induction was required in 35 (31.8%) patients. There was successful induction in 1 (9.1%) of patients. At five minutes 101(91.8%) of neonates showed good apgar i.e. >7. Both groups were compared among each other in terms of both quantitative and qualitative variables. The onset of spontaneous labor, success of IOL and good apgar score at 5 minutes were compared among groups. The was significant difference among groups A and B in terms of these parameters except good apgar score i.e. p values of 0.008, 0.021 and 0.297 for spontaneous labor, IOL and good apgar scores Good apgar score at 5 min was not statistically significant among any stratification group. Conclusion: The consumption of dates significantly improves the fetomaternal outcomes in primigravida term pregnancies. The results should be validated in large randomized controlled trials. Keywords: Date fruit, Labour outcomes, Labour progression.